On Constructing a Scientific Archives Network: Exploring Computational Approaches to the Cybernetics Thought Collective - Anderson, Bethany G. (Archivaria)

(untitled) (Association of Canadian Archivists, 2021)
Computational approaches to archives present archivists and users with new ways of engaging with records and their provenance. Such approaches are particularly useful for scientific archives due to the collective and collaborative nature of modern scientific knowledge production. This article explores computational approaches to digitized fonds of scientists involved in the transdisciplinary scientific movement cybernetics through the Cybernetics Thought Collective: A History of Science and Technology Portal Project as a means to reveal the ways cyberneticians have developed concepts and debated ideas through the creation and exchange of correspondence and other records. The project has experimented with machine-learning and natural-language-processing tools to generate data from the materials in an effort to reveal connections between the cyberneticians and their correspondence. Cybernetics seeks to understand the human condition through experiments with machines, and, in a cybernetically inspired sense, so too do archivists seek to understand their archives through experiments with machines. Such explorations are important for documenting scientific thought collectives like cybernetics in a digital age.